Rehabilitasi Kardiovaskular Di Indonesia - Basuni Basuni; Andang H Joesoef; Dede Kusmana (Jurnal Kardiologi Indonesia, 2009)
“A process by which a person is restored to an optimal physical, medical, psychological, social, emotional, sexual, vocational and economic status.” Itulah definisi Cardiac Rehabilitation dari WHO tahun 1969, yang kemudian ‘disempurnakan’ pada saat ini dengan memperhatikan dasar penyakit, proses dan kondisi pasca sakit. Definisi tersebut dijabarkan dalam definisi terkini yaitu:“The rehabilitation of cardiac patients is the sum of activities required to influence favourably the underlying cause of the disease, as well as the best possible physical, mental and social conditions, so that they may by their own efforts, preserve or resume when lost, as normal a place as possible in the society”.